PENGEMBANGAN PURWARUPA KURSI RODA STATIS DENGAN LINGKUNGAN MAYA TERPADU UNTUK PERANGKAT REHABILITASI MEDIS - Sulistyo Dharmawan, Haryo
According to World Health Organization, in 2011 as much as 15% of the population of the world receive all sorts of disabilities. One of the illnesses that causes a lot of disabilities is stroke. Those who got it at the age of 60 and above, as much as 13.9% of them has total dependency on aid apparatuses. Stroke is a sickness that is caused by the hindering of blood circulation into some parts of the brain. This blockage may be caused by two occurrences, blockage (ischemic stroke) or rupture (hemorrhagic stroke) of the blood vessels leading to the brain. One of the many effects of a stroke include Unilateral Spatial Neglect (USN), which is the loss of perception towards a stimulus from a certain direction or certain region of their perception space. One study said that the use of Virtual Reality as an assessment tool for neglect is more sensitive compared to the conventional pen-and-paper tests due to its ability to produce a moving stimulus without any actual movement. Even though there are many studies about the application of Virtual Environment in medical rehabilitation, it is still scarcely used to the upmost of its potential in public use. For that reason, in this final project a simulator for a static wheelchair that is integrated with Virtual Environment will be developed to explore the potentials of virtual environment in its rehabilitation capabilities. The static wheelchair simulator will be developed in three big parts, which is applicative virtual environment for rehabilitation of the use of powered wheelchair, the static wheelchair simulator and how it works, and how to connect the powered wheelchair into the virtual environment which will be done by measuring the speed of each wheel of the wheelchair and using Uduino for serial communication into Unity. The user’s maneuverability in the virtual environment will be measured by calculating their Root Mean Square of Least Errors (RMSLE) towards a testing line apparent on the virtual environment, and the number of collisions that happened during testing. User’s experience is also measured by using a questionnaire that asks the difficulty in moving and using the Simulator Sickness Questionnaire (SSQ). The test begins with an accuracy test and is followed with a pilot test with six participants. The developed simulator is found to have an error of 1.92% for a straight motion, 1.93% for turning right, and 1.34% for turning left. An overall decreasing average score of RMSLE from 0.37 to 0.22, decreasing average number of collisions from 31.83 to 13.50, increasing total score of SSQ from 21.19 to 63.58, and a decreasing scale of difficulty on maneuvering the wheelchair straight from 5.50 to 1.50 and maneuvering the wheelchair to turn from 5.33 to 2.50 are observed as the tests go on. Some participants chose to drop out of the tests because of the discomfort caused by simulator sickness, with only two participants able to go on and finish the test four times.